Social Interaction in Hunter-Gatherer Societies: Simulating the Consequences of Cooperation and Social Aggregation. (June 2014) - Barceló, Juan A.; Bernal, Florencia Del Castillo; Olmo, Ricardo del; Mameli, Laura; Quesada, F. J. Miguel; Poza, David; Vilà, Xavier
This article describes the design and operation of an agent-based model that represents aspects of hunter-gatherer subsistence, technology, and cultural identity. The agents (representing families or households) in the model interact in a world that has a seasonally variable resource density. Agents must collect resources every step, either independently (by "gathering") or with cooperation from neighboring agents ("hunting"). Several parameters affect cooperation: understanding these effects is one of the main focus of this article. Another focus is understanding the effects of cooperation in terms of cultural diversity/homogeneity. Some input parameters are historically and ethnographically calibrated, and the results are contrasted, with ongoing archaeological research of Patagonian hunter-gatherers (from 7000 BC or even earlier to 19th century). Specific research questions include how do processes of convergence and divergence occur between groups of hunter-gatherers over the long term? How could the autonomous local interactions of heterogeneous bounded rational agents generate this kind of regularity? What role outside influence plays on the formation of ethnic identities? Our aim is to integrate the state-of-the-art knowledge from different social sciences and technological developments into a fruitful approach to develop sociohistorical studies